The influence of sock composition on the appearance of foot blisters in hikers - Chicharro-Luna, Esther; Gijón-Noguerón, Gabriel; Sanchez-Rodriguez, Raquel; Martínez-Nova, Alfonso (Elsevier, 2022)
Introduction: Socks are of fundamental importance in reducing friction and in controlling the temperature and humidity of the foot, thus preventing the appearance of blisters. However, the influence of sock fibres (synthetic vs. natural) on blistering during long-distance hiking has received little research attention. Aims: This study evaluates the influence of sock fibres on the appearance of foot blisters in hikers. Method: The sample consisted of 203 male and female hikers, mean age 35.8 ± 14.5 years, from 22 countries. All were interviewed and assessed at shelters on the French route of the Camino de Santiago (Spain). Sociodemo- graphic and clinical data were obtained for each hiker; other study data included the number of blisters on the foot, whether the socks were wet at the end of the day, the model of sock used and the nature of its constituent fibres. Results: Among the hikers interviewed, 68.5% presented foot blisters. 74.2% used socks with predominantly synthetic fibres, compared to 25.9% whose socks were mainly composed of natural fibres. On average, they had walked 253.7 km. Hiking in wet socks was associated with a 1.94 times greater risk of experiencing foot blisters (95% CI 1.04–3.61) (p = 0.035). Multivariate analysis showed that the proportion of natural/synthetic fibres in the composition of the sock was not related to the presence of blisters. Conclusions: The use of wet socks heightens the risk of foot blisters in hikers, but the composition of the sock is not associated with blistering. We recommend hikers change their socks in long stages to maintain feet dry and so avoiding the appereance of blisters
Keywords: Pies-Lesiones y heridas; Fibras textiles; Senderismo; Blisters; Thermoregulation; Foot; Socks Fibres